2003
DOI: 10.1097/00001721-200312000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A new activated factor X-based clotting method with improved specificity for procoagulant phospholipid

Abstract: An improved activated factor X-based clotting method was used to investigate activity of procoagulant phospholipid (PPL) in blood samples collected into various anticoagulants and in plasmas with a range of abnormalities. The dilute activated factor X-activated clotting time (XACT) was carried out on a mixture of specimen with phospholipid-free porcine plasma. PPL from the test sample is then rate-limiting, controlling the clotting time so that the XACT is shortened from a maximum of approximately 120 s with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 25 publications
2
42
0
1
Order By: Relevance
“…To overcome this technical challenge, we generated BDMPs from the brains of adult C57BL/6J mice by freeze-thawing injury. 37 The BDMPs thus produced resemble those detected in the plasma of FPI mice in size and levels of PS and GFAP expression (supplemental Figure 7). When viewed under TEM, these BDMPs were irregular spheres of 50 to 500 nm in diameter, with a clearly defined and relatively intact membrane, but without apparent granules (Figure 2A).…”
Section: Procoagulant Activity Of Bdmpsmentioning
confidence: 74%
See 1 more Smart Citation
“…To overcome this technical challenge, we generated BDMPs from the brains of adult C57BL/6J mice by freeze-thawing injury. 37 The BDMPs thus produced resemble those detected in the plasma of FPI mice in size and levels of PS and GFAP expression (supplemental Figure 7). When viewed under TEM, these BDMPs were irregular spheres of 50 to 500 nm in diameter, with a clearly defined and relatively intact membrane, but without apparent granules (Figure 2A).…”
Section: Procoagulant Activity Of Bdmpsmentioning
confidence: 74%
“…The first was a PS-dependent assay that tested the ability of BDMPs to promote clot formation in the presence of coagulation factor Xa. 37 For each reaction, 25 mL of phosphate-buffered saline (PBS) containing a known number of BDMPs was mixed with 25 mL of phospholipid-deficient porcine plasma (IMVS, Adelaide, Australia) and 100 mL of bovine factor Xa (0.02 U/mL in a buffer containing 15 mM CaCl 2 , 100 mM NaCl, 20 mM N-2-hydroxyethylpiperazine-N9-2-ethanesulfonic acid, and 0.001% polybrene [pH 7.0]). Clot formation was monitored at 37°C on a CoaScreener coagulation analyzer (American Labor Corp., Durham, NC).…”
Section: Coagulation Assaysmentioning
confidence: 99%
“…Blood samples were collected at multiple points after mice were subjected to FPI (1.9 6 0.1 atm) to measure the dynamic state of coagulation (supplemental Methods, available on the Blood Web site) 12,14,15 and the production of BDMPs and anti-brain antibodies. To test the procoagulant activity of CL and mtMPs without the confounding influence of brain trauma, uninjured C57BL/6J mice (12-16 weeks and 22-25 g; The Jackson Laboratory, Bar Harbor, ME) were injected through the tail vein with bovine heart CL (Avanti Polar Lipids, Alabaster, AL), mouse mtMPs, or phosphate-buffered saline (PBS; pH 7.4).…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Moreover, Joop and coworkers used FCM and suggested that the PDMP level is simply a reflection of the platelet count 16) . Therefore, according to the findings of several studies, the PDMP/Plts ratio should be a constant value, regardless of the presence of thrombopenia [40][41][42] . In our study using ELISA, the thrombopenia group has significantly elevated PDMP values, and there was a weak but significant negative correlation between the max PDMP value and the nadir platelet count.…”
Section: Conflicts Of Interestmentioning
confidence: 99%